Calendar age and puberty-related development of regional gray matter volume and white matter tracts during adolescence - Ando, Ayaka; Parzer, Peter; Kaess, Michael; Schell, Susanne; Henze, Romy; Delorme, Stefan; Stieltjes, Bram; Resch, Franz; Brunner, Romuald; Koenig, Julian (Brain structure & function, 2021)
Adolescence is a critical time for brain development. Findings from previous studies have been inconsistent, failing to distinguish the influence of pubertal status and aging on brain maturation. The current study sought to address these inconsistencies, addressing the trajectories of pubertal development and aging by longitudinally tracking structural brain development during adolescence.
Gesehen am 04.01.2023